Social Media Advertising And Consumer Decision making In The Fashion Industry - Asiedu, F.O. (University of Ghana, 2017)
Social media advertising is a powerful tool in contemporary times. The study sought to explore the effectiveness of firms’ social media advertising of fashion brands on consumer decisionmaking with the mediating effect of consumer engagement in Ghana. Three constructs in assessing the effectiveness of firms’ social media advertising which included emotional appeal, informativeness and advertising creativity were used. There were two objectives of the study. The first objective was to determine the relationship between social media advertising constructs and consumer decision-making. Another objective was to determine the mediating role of consumer engagement on social media advertising constructs and consumer decisionmaking. The study employed exploratory and confirmatory factor analyses along with structural equation modelling to evaluate a proposed model for understanding the relationships among the constructs and to examine the mediating effects. The findings indicated that there was no significant relationship between emotional appeal in social media advertising and consumer decision-making. And as a result, there was no mediation of consumer engagement in the relationship. Again, there was a significant relationship between informativeness in social media advertising and consumer decision-making and consumer engagement partially mediated the relationship. In addition, there was a significant relationship between advertising creativity in social media advertising and consumer decision-making and consumer engagement fully mediated the relationship. Thus, apart from emotional appeal, informativeness and advertising creativity in social media advertising affected the decisions that consumers make. Furthermore, consumer engagement influenced the relationship between informativeness and advertising creativity in social media advertising and consumer decisionmaking. Therefore, consumer engagement which is the responses of consumers to brand – related content such as likes and comments influenced the decisions that other consumers made based on informativeness and advertising creativity in social media advertising.
Thesis (MPhil)
Keywords: Social Media Advertising; Consumer; Decision making; Fashion Industry